Link quality aware routing algorithm in mobile wireless sensor networks [electronic resource] - Ribwar Bakhtyar Ibrahim, 1982- (2013)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2013